Targeted kinase inhibition relieves slowness and tremor in a Drosophila model of LRRK2 Parkinson's disease. (December 2017) - Cording, Amy; Shiaelis, Nicolas; Petridi, Stavroula; Middleton, C.; Wilson, Laurence; Elliott, Christopher
Abstract In a number ofDrosophila models of genetic Parkinson's disease (PD) flies climb more slowly than wild-type controls. However, this assay does not distinguish effects of PD-related genes on gravity sensation, "arousal", central pattern generation of leg movements, or muscle. To address this problem, we have developed an assay for the fly proboscis extension response (PER). This is attractive because the PER has a simple, well-identified reflex neural circuit, in which sucrose sensing neurons activate a pair of "command interneurons", and thence motoneurons whose activity contracts the proboscis muscle. This circuit is modulated by a single dopaminergic neuron (TH-VUM). We find that expressing either theG2019S orI2020T (but notR1441C, or kinase dead) forms of humanLRRK2 in dopaminergic neurons reduces the percentage of flies that initially respond to sucrose stimulation. This is rescued fully by feedingl -DOPA and partially by feeding kinase inhibitors, targeted to LRRK2 (LRRK2-IN-1 and BMPPB-32). High-speed video shows thatG2019S expression in dopaminergic neurons slows the speed of proboscis extension, makes its duration more variable, and increases the tremor. Testing subsets of dopaminergic neurons suggests that the single TH-VUM neuron is likely most important in this phenotype. We conclude theDrosophila PER provides an excellent model ofLRRK2 motor deficits showing bradykinesia, akinesia, hypokinesia, and increased tremor, with the possibility to localize changes in neural signaling. Disease models: A reflex reaction A simple reflex in flies can be used to test the effectiveness of therapies that slow neurodegeneration in Parkinson's disease (PD). Christopher Elliott and colleagues at the University of York in the United Kingdom investigated the contraction of the proboscis muscle which mediates a taste behavior response and is regulated by a single dopaminergic neuron. Flies bearing particular mutations in the PD-associated gene leucine-rich repeat kinase 2 (LRRK2) in dopaminergic neurons lost their ability to feed on a sweet solution. This was due to the movement of the proboscis muscle becoming slower and stiffer, hallmark features of PD. The authors rescued the impaired reflex reaction by feeding the fliesl -DOPA or LRRK2 inhibitors. These findings highlight the proboscis extension response as a useful tool to identify other PD-associated mutations and test potential therapeutic compounds.